Improving ryegrass‐clover pasture dry matter yield and urea efficiency with gibberellic acid. (25th February 2014) - Zaman, Mohammad; Ghani, Anwar; Kurepin, Leonid V; Pharis, Richard P; Khan, Shabana; Smith, Terry J
Abstract BACKGROUND The effects of spraying gibberellic acid (GA3) at 20 or 30 g ha−1, with or without application of urea, on pasture dry matter (DM) yield, herbage nitrogen (N) concentration and feed quality were investigated in 2011 and 2012 for managed pastoral systems in New Zealand across a range of sites, in both autumn and spring. RESULTS On the Waikato site (autumn and spring, 2012), and at all five sites in 2011, liquid urea applied with GA3 at 20 or 30 g ha−1 consistently produced significantly higher pasture shoot DM yield, relative to liquid urea alone. Application of GA3 alone reduced feed quality by lowering metabolizable energy, crude protein and organic matter digestibility values. However, a reduced feed quality was not observed when GA3 was applied together with liquid urea. Liquid urea applied with GA3 also reduced total N and nitrate‐N concentration in herbage, relative to liquid urea applied alone. CONCLUSION Application of GA3 together with liquid urea provides an opportunity for the strategic use of urea to meet both production and environmental goals. © 2014 Society of Chemical Industry